Evenness and diversity in Upper Cambrian – Lower Ordovician trilobite communities from the Central Andean Basin (Cordillera Oriental, Argentina) - Balseiro, Diego (2013)
Community evenness has recently received much attention, either because it is related to ecosystem functioning or because it may affect estimation of diversity. Temporal and environmental trends in diversity and evenness of trilobite communities during the Late Cambrian – Early Ordovician of the Cordillera Oriental (north-western Argentina) are here analysed. Richness and evenness increase through time in both deep subtidal (between fair-weather and storm wave base) and offshore (below storm wave base) communities. Two significant patterns are superimposed on this general trend: (1) the magnitude of the increase in evenness is much more pronounced in deep than in shallower settings, and (2) richness and evenness trajectories are decoupled (while a significant rise in evenness is recorded in the middle Tremadocian (Tr2), an increase in richness is delayed until the late Tremadocian (Tr3)). In contrast to expectations, a single family (Olenidae) is dominant in samples associated with this earlier rise in evenness relative to richness. Hence, this trend is explained neither by the number of families present in the communities nor by the familial identity of the most abundant taxon. Large-scale comparisons of the timing and geographical components of these trends are restricted to the patterns recognized in Laurentian North American studies. Results from the Cordillera Oriental mirror those of Laurentia regarding the rise in both metrics in deep marine settings. Nevertheless, the timing of this increase in richness and evenness is delayed in the Cordillera Oriental, supporting the idea that palaeogeographical regions differed in the nature and timing of ecological changes. Finally, the rise in trilobite alpha-diversity through the Late Cambrian – Early Ordovician of the Cordillera Oriental supports the idea that trilobite alpha-diversity did not decline worldwide, suggesting that the relative decline in trilobite alpha-diversity is most probably caused by the dilution effect.